In vitro Prebiotic Bacterial Growth Properties of Xylooligosaccharides Produced by Autohydrolysis of Corn Fiber - Samala, Aditya; Srinivasan , Radhakrishnan; Brooks, John P.; Sharma, Chander S. (International Journal of Poultry Science, 2015)
Xylooligosaccharides (XOS) are considered to be prebiotics. Prebiotics are defined as the non-digestible food ingredients that benefit the host by stimulating the growth and activity of a limited number of bacteria, such as the Bifidobacterium genus, in the intestine. The objective of this study was to evaluate prebiotic properties for XOS produced by autohydrolysis of corn fiber. We compared commercial XOS (XOS-C), fructo-oligosaccharides (FOS), inulin, monosugars (xylose and glucose) and control (no sugars), with auothydrolysis liquor containing XOS (XOS-D) for the growth of Bifidobacterium breve, B. adolescentis and Lactobacillus brevis. Optical density at 550 nm (OD550) was normalized by taking logarithm of ratio of OD on particular day to OD on day 0, for each organism/substrate/media combination. Normalized optical density is referred to as specific growth. Growth on commercial XOS (XOS-C) was comparable with growth on other prebiotics (FOS and inulin). XOS-D promoted growth more than that of the control. For XOS-D, highest growth recorded was for L. brevis (0.461) followed by B. breve (0.267) and B. adolescentis (0.263). XOS-D performance was comparable to FOS and inulin for L. brevis. XOS produced from corn fiber exhibit the potential to be used as a prebiotic in poultry.